العوامل المؤثرة في تقبل الفصول الافتراضية لدى طلبة كلية التربية الأساسية بالكويت في ضوء نموذج قبول التقنية TAM - Factors influencing the acceptance of virtual classes among students of the Faculty of Basic Education in Kuwait in light of the TAM technology acceptance model - Mohammed Mane’ al-Qahtani, Saeed Saad; Sahrir, Muhammad Sabri (Centre for Core Studies, KUIS, Selangor, 2020)
من أهم معايير نجاح استخدام التكنولوجيا في التعليم هو رضى المستفيدين منها وتقبلهم لها. لذا هدف هذا البحث إلى الكشف عن العوامل المؤثرة على تقبل الفصول الافتراضية لدى طلبة كلية التربية الأساسية في دولة الكويت في ضوء نموذج قبول التقنية TAM . ولتحقيق أهداف البحث واختبار فرضياته، تم استخدام المنهج المسحي، واختيار عينة قصدية بلغت ) 400 ( من طلبة كلية التربية الأساسية في الكويت خلال الفصل الأول من العام الجامعي 2018 - 2019م، وتمثلت أدوات البحث في إعداد وتصميم استبانة تكونت من ثلاثة أجزاء رئيسية، وبعد جمع بيانات البحث وتحليلها احصائياً أثبتت النتائج وجود علاقة إيجابية بين النية لاستخدام الفصول الافتراضية وعوامل الفائدة المحققة وسهولة استخدام تقنية التعليم المتاحة في الفصول الافتراضية لدى طلبة كلية التربية الأساسية في الكويت، وكذلك علاقة إيجابية بين العوامل المستقلة) الدعم الفني، التفاعل في التعليم، والكفاءة الذاتية (والفائدة المحققة، وسهولة استخدام تقنية التعليم المتاحة في الفصول الاف تراضية لديهم، وعلاقة إيجابية أيضاً بين العوامل المستقلة الدعم الفني، التفاعل في التعليم والكفاءة الذاتية( ونية الطلبة حول استخدام الفصول الافتراضية من خلال الفائدة المحققة وسهولة الاستخدام كعوامل وسيطة لدى الطلبة، إلا أنه لا يوجد تأثير لنوع جنس الطلبة في قبولهم لاستخدام التقنيات المتاحة في الفصول الافتراضية، ويوجد تأثير للخبرة في ذلك، وتم الانتهاء بذكر عدد من التوصيات التطبيقية لنتائج البحث. ***************************************************************************** The successful use of technology in education relies primarily on the satisfaction and acceptance of its beneficiaries. This research aims to reveal the factors influencing the understanding of students of Faculty of Education in Kuwait for the virtual classrooms in the light of their acceptance for the TAM Technique. Survey methodology and selection of 400 students from Faculty of Education in Kuwait as a sample during the first semester in the academic year 2018-2019 are two methods used to achieve the goals of the research and test its hypotheses. The research develops a questionnaires consists of three major parts. After collecting and analysing the data statistically ,the results proves that there is a positive relationship between the intent of using virtual classrooms, usefulness factors and the ease of using technical education in virtual classrooms for the students in Faculty of Education in Kuwait. The research also shows that there is a positive relationship betweet the independent factors such as (technical support, interactions in teaching and self-efficacy) and the usefulness and the ease of using technical education in virtual classrooms for the students. Another positive relationship is discussed by this research connects the independent factors (technical support , interactions in teaching and self-efficacy) , the students' intention of using the virtual classrooms through the usefulness and the ease of use as a feedstock for them. Besides , it is indicated that the gender of the students has no effection in their acceptance for using the information technology in virtual classrooms however the experience palys a vital role in that. The research concludes with a mention of some applied recommendations for the results of this research.